Ten chudy Schlechter - Maleszyńska, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article relates the life and work of a pre-war author who is almost unknown by name, but very popular because of his work, an author of songs, cabaret sketches, and film scrips. He was born in a family of assimilated Jews from Lviv. He made a great contribution to Polish language, both literary and colloquial, by writing song lyrics with phrasings that have become fixed expressions used in communication of the simplest and most universal feelings. Schlechter became a victim of the Holocaust, and his artistic work, which focused on joy and the bright side of life, did not protect him physically and mentally from the Nazi death machine. He was killed in Lviv ghetto, probably in 1943.